“Music is my life”: Examining the connections between music students’ workload experiences in higher education and meaningful engagement in music - Jääskeläinen, Tuula (SAGE, 2022)
Enhancing our knowledge about students’ experiences during their studies in higher music education is essential to understand and support them as they cope with their specific workloads in studying music. This study provides a research-based understanding of what engaging in music means to music students when they reflected on their experiences of their studies and workloads. The data were collected from interviews with 29 students in higher music education institutions in Finland and the United Kingdom, and the analysis was conducted by following the framework of transcendental phenomenology. Music students’ experiences of their workload are connected in multifaceted ways to the meanings they ascribe to their engagement in music, such as intense and complex experiences that are also a source of vitality, their development as musicians, their creative self-expression, their interaction with others and in building a community, their personal growth and coping approaches during their studies, and the transcendental experiences they encounter during their engagement with music. Thus, the findings indicate that engaging in music is a holistic experience for music students. This study shows the importance of understanding and investing in music students’ unique workload experiences through research on the teaching and learning practices of higher music education institutions, which can in turn support music students’ well-being, learning, and future careers.
Keywords: musiikkikasvatus; korkeakouluopiskelu; oppiminen; kokemukset